Implementation of plurilingual approach into the foreign language teaching - Straková Zuzana (Journal of Language and Cultural Education, 2020)
Teaching foreign languages has adopted various approaches over the history. The last decades of dominance of the Communicative language teaching brought the tendency to insist on the target language use in the classroom in order to allow the immersion into the language. The European Union, however, started to support linguistic diversity more than two decades ago and it has left an imprint on the way foreign language teaching is approached today. Inclusion of plurilingualism in traditional school context requires the readiness of language teachers to use other languages as well as encourage learners to use their prior language experience. The present study presents the results of a questionnaire survey among student teachers measuring their attitudes and readiness to implement more than one additional language in their practice. The participants of the study (n = 118) are all future teachers of English language at both undergraduate and graduate level. The results of the survey indicate a generally positive attitude towards plurilingualism and at the same time ability of the students to rely on more than one language while teaching. The results, however, raise quite a few questions and imperatives for the content of teacher training programmes as well as for the organisation of language education in general.